ACUTE ABDOMINAL PAIN IN PEDIATRIC PRACTICE - O.V. Karaseva (Union of pediatricians of Russia, 2011)
The fate of the patient often depends on the ability of doctors to interpret the pain that has arisen in the abdomen. The paper gives a detailed analysis of the pathogenesis of abdominal pain and arranges the main causes of the «acute abdomen» in children. Particular attention is paid to the differential diagnosis of the acute surgical abdominal diseases in children. The structure of the syndrome of «acute abdomen» in children over 1 year in hospital emergency clinic has been analyzed. Key words: children, acute abdomen, pain, abdominal pain, causes, diagnosis, differential diagnosis, acute appendicitis, intestinal invagination. (Pediatric Pharmacology. - 2011; 8 (5): 21-27.)